2020
DOI: 10.1002/jsfa.10517
|View full text |Cite
|
Sign up to set email alerts
|

Effect of low‐temperature vacuum heating on physicochemical properties of sturgeon (Acipenser gueldenstaedti) fillets

Abstract: BACKGROUNDSturgeon is popular for its nutritious value and its taste. However, sturgeon fillets are traditionally heated in 100 °C boiling water, resulting in unfavorable taste and with a negative effect on the quality. This study considered the effect of combinations of vacuum and low‐temperature treatments (LTVH groups) on sturgeon fillets compared with the traditional heat treatment (TC groups).RESULTSThe results show that the LTVH groups had lower cooking‐loss rates. All LTVH fillets were changed to a whit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 45 publications
1
15
0
Order By: Relevance
“…The thermal treatment of sturgeon fillets was prepared by a self‐built laboratory equipment according to our previous study (Cai et al ., 2020). And the groups were performed in Table 1.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The thermal treatment of sturgeon fillets was prepared by a self‐built laboratory equipment according to our previous study (Cai et al ., 2020). And the groups were performed in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…The extraction of myofibrillar protein was performed according to the method of Cai et al . (2020) and the content of protein and glucose in vitro model were prepared as Li et al . (2018)’s study, as well as the experimental design were shown in Table 1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous study showed that the LTVH method can reduce the oxidation of protein and lipid in fillets, compared to those observed in the context of traditional domestic cooking (100°C boiling water) . [13] Additionally, the LTVH fillets had agreat shelf life after 7 days storage, performing abetter storage quality than the control groups thermal treatment at 100°C boiling water . [14] However, there is still limited data available on the water-holding capacity and tenderness of sturgeon fillets after processing via different heating time/ temperature combinations.…”
Section: Introductionmentioning
confidence: 91%
“…Myofibrillar proteins are the most abundant proteins in the sturgeon (Acipenser gueldenstaedti) fillets, constituting approximately 50-55% of the total protein content . [13] Therefore, changes in the myofibrillar proteins during thermal treatment play an important role in the alteration of the characteristics of sturgeon fillets. In daily life, we usually judge the readiness of cooked fillets based on their visual appearance and color.…”
Section: Extraction Rate Of Myofibrillar Proteinsmentioning
confidence: 99%